Behavior of olive (Olea europaea L) cultivars for oil under deserted conditions in Sonora - Grijalva Contreras, Raúl Leonel; Macías Duarte, Rubén; López Carvajal, Arturo; Robles Contreras, Fabián; Navarro Ainza, José Cristóbal (Revista Mexicana de Ciencias Agrícolas, 2018)
In Mexico, the behavior of olive cultivars under desert conditions is unknown. In the present study evaluated six Italian olive cultivars for oil (Nocellara Messinese, Nocellara Belize, Carolea, Coratina, Leccino and Grossa di Cassano) and compared to Manzanillo as a witness, which is intended for table olives. The work was conducted in the Experimental INIFAP in Caborca, Sonora during the years 2001-2010. The cultivars were planted at a spacing of 8 x 8 m (156 trees ha-1) and drip irrigation. Italian cultivars were more to start f lowering late (6-13 days) and to reach the fruit ripening (22-88 days) with respect to Manzanillo. There weresignificantdifferencesinfloraldensitywerehigherin Manzanillowithflowers3420cm-2anddifferenceinfruitset Coratina sticking with 4.15%. Yield and oil content showed significant differences among cultivars. Olive average yield in the first six years of production varied from 10.5 to 4.3 t ha-1 Messinese Nocellara; on the other hand, the oil content was higher in Carolea with 17.5% followed by 12% Manzanillo were the two cultivars with largest yield of oil with 1 557.5 and 960 kg ha-1. In all cultivars was obtained extra- virgin oil polyphenol content ranged from 117.5 ± 4.4 to 215.4 ± 12.3 meq of caffeic acid. In any growing pest problems arose or diseases.
Keywords: Olea europaea L.; oil quality; oil content; productivity; varieties